Activity-based mindfulness: large-scale assessment of an online program on perceived stress and mindfulness - Timm, Eliane; Ko, Yobina Melanie; Hundhammer, Theodor; Berlowitz, Ilana; Wolf, Ursula (Frontiers in Psychology, 2024)
Background and objective Mindfulness has emerged as key construct in mental health over past decades. While current mindfulness-based interventions (MBIs) are usually rooted in Asian contemplative traditions, mindfulness practices can equally be found in other knowledge systems, including integrative medicine systems such as anthroposophic medicine (AM). The Activity-Based Stress Release (ABSR) program incorporates the latter as part of an 8-week-long online intervention combining mindfulness exercises, behavioral self-observation, and mindful movement practices derived from this integrative medicine frame. The program could offer additional means for cultivating mindfulness, thereby addressing the necessity for diverse approaches in conjunction with individual differences, diverse clinical demands, or restricted capacities to perform certain mindfulness practices. Using an observational repeated-measures design, the current study aimed to assess a large-scale online implementation of this program in terms of its feasibility, assessing perceived stress and mindfulness. Method Individuals who enrolled in any of the 37 ABSR program iterations carried out during 2023 and agreed to participate in the study completed online surveys including validated stress and mindfulness scales at the beginning, middle, end, and follow up of the intervention. Linear-mixed models were used for data analysis. Results A total of 830 individuals took part in the study, of which 53.5% filled in at least 2 surveys. In line with our expectation, mindfulness scores increased significantly over the course of the intervention, while stress scores decreased significantly in this timeframe. We further found differential effects of self-practice frequency and duration on the outcomes. Conclusion This study provides a first indication of stress reduction in conjunction with the online implementation of this novel MBI. The work further suggests that this AM-based intervention indeed targets mindfulness, as do other MBIs, and that it is adaptable to an online format. However, given the observational single-arm design, controlled studies will be necessary to confirm these results. Nonetheless, the study adds a novel contribution to existent MBIs, which is significant in view of the need for diverse approaches to meet the heterogeneity of individual predispositions and clinical requirements. It remains to established by forthcoming research for which groups of individuals or clinical features this approach could be especially beneficial or less suitable.